Real-time 3D biomechanical analysis and AI personal trainer for strength and conditioning exercises using markerless motion capture - Steyn, Lize (Stellenbosch : Stellenbosch University, 2025)
Steyn, L. 2025. Real-time 3D Biomechanical Analysis and AI Personal Trainer for Strength and Conditioning Exercises Using Markerless Motion Capture. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/9869923a-a8bb-4eaa-a304-c38e39c71061